(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2025)
Introduction: Lifestyles can lead individuals to a healthy life, but if healthy habits are not adopted it also leads to functional deterioration of people. Therefore, lifestyles constitute a challenge and priority in public health. Objective: To evaluate the lifestyles of the inhabitants of the city of Monteria. Methods: A cross-sectional analytical study was carried out with a consolidated sample of 685 inhabitants of the city of Monteria, of whom 415 were female and 270 males. The average age was 26.1 ± 11.2 years. Lifestyles were evaluated with the short version of the IPAQ and FANTASTICO questionnaires. Results: 71.2% of the women did not comply with the levels of physical activity per week and 58.8% of the men did not comply with the international recommendations. However, an association was found between the sex of the participants and physical activity levels, (p=0.001). Regarding lifestyles, an association was observed with the sex of the subjects showing significant differences (P=0.039). Sex was not significantly related to sedentary behavior (P=0.296). Conclusion: Most of the lifestyle domains showed a need for change in both men and women. The results where there is greater alertness to generate behavioral changes are health control and sexual behavior, physical activity, nutrition and introspection. Key words: Lifestyles, quality of life, habits, health.